Translation, Cultural Adaptation, and Preliminary Validation of the “Palliative Care and Rapid Emergency Screening Tool” into European Portuguese - Cristiana Rolão; Paulo Reis-Pina (Acta Médica Portuguesa)
The aim of this study was to translate, culturally adapt, and conduct a preliminary validation of the “Palliative Care and Rapid Emergency Screening Tool” into European Portuguese for use in the emergency department. The tool was developed to assist healthcare professionals in identifying patients with palliative needs, ensuring timely referrals for palliative care consultation. The translation and adaptation process followed established guidelines for cross-cultural adaptation. Content validity was assessed by eight experts in palliative care, who confirmed that the tool was clear, relevant, and easy to understand. Face validity was evaluated by ten emergency department professionals, who rated the tool highly in terms of clarity and applicability to the target population. The study found that the tool effectively addresses key domains in palliative care, offering a simple and practical approach for use in the emergency care setting. These findings suggest that the “Instrumento de Triagem Rápida para Cuidados Paliativos no Serviço de Urgência” (PALinSU) can potentially enhance the identification of palliative care needs, leading to improved patient care and timely referrals.